Evaluasi Perparkiran Dibadan Jalan (On Street Parking) Terhadap Kinerja Jalan Dikawasan Jl. Agus Salim Kota Malang - Tonsa , Samuel; Arifianto, Andy Kristafi; Rahma , Pamela Dinar (Fakultas Teknik Universitas Tribhuwana Tunggadewi, 2023)
On-street parking in Malang City still causes many complicated problems in structuring parking on the road, this is because there are still many illegal parking attendants. In addition to management problems, parking on the road also causes traffic problems as seen from the many traffic jams caused by parking vehicles that take up the road. So this research with the title Evaluation of on-street parking on road performance in the area Jalan Agus Salim Malang City. Researchers aim to analyze the problems in on-street parking on the performance of Jalan Agus Salim Malang City. This paper is analyzed using the Directorate General of Land Transportation, which includes various parking features, among others: parking volume, parking accumulation, parking capacity, parking index, parking turnover, parking duration. From the results of the analysis using research data obtained from observations and data collection for one week, the authors can draw the following conclusions: (1) Parking needs on Jalan Agus Salim, Malang City, namely for the need for two-wheeled vehicle parking lots require 5074 parking plots/day, and for four-wheeled parking needs require 1342 parking plots/day, and (2) Provision of existing parking plots for two-wheeled 167 parking plots and for four-wheeled 33 parking plots, so the need for plots exceeds the existing provision.